Function of miR-146a-5p in Tumor Cells As a Regulatory Switch between Cell Death and Angiogenesis: Macrophage Therapy Revisited - Simanovich, Elina; Brod, Vera; Rahat, Maya M.; Rahat, Michal A. (Frontiers in Immunology, 2018)
Tumors survive and progress by evading killing mechanisms of the immune system, and by generating a tumor microenvironment (TME) that reprograms macrophages in situ to produce factors that support tumor growth, angiogenesis, and metastasis. We have previously shown that by blocking the translation of the enzyme inducible nitric oxide synthase (iNOS), miR-146a-5p inhibits nitric oxide (NO) production in a mouse renal carcinoma cell line (RENCA), thereby endowing RENCA cells with resistance to macrophage-induced cell death. Here, we expand these findings to the mouse colon carcinoma CT26 cell line and demonstrate that neutralizing miR-146a-5p’s activity by transfecting both RENCA and CT26 cells with its antagomir restored iNOS expression and NO production and enhanced susceptibility to macrophage-induced cell death (by 48 and 25%, respectively, p < 0.001). Moreover, miR-146a-5p suppression simultaneously inhibited the expression of the pro-angiogenic protein EMMPRIN (threefolds, p < 0.001), leading to reduced MMP-9 and vascular endothelial growth factor secretion (twofolds and threefolds, respectively, p < 0.05), and reduced angiogenesis, as estimated by in vitro tube formation and scratch assays. When we injected tumors with pro-inflammatory-stimulated RAW 264.7 macrophages together with i.v. injection of the miR-146a-5p antagomir, we found inhibited tumor growth (sixfolds, p < 0.001) and angiogenesis (twofolds, p < 0.01), and increased apoptosis (twofolds, p < 0.01). This combination therapy increased nitrites and reduced TGFβ concentrations in tumor lysates, alleviated immune suppression, and allowed enhanced infiltration of cytotoxic CD8+ T cells. Thus, miR-146a-5p functions as a control switch between angiogenesis and cell death, and its neutralization can manipulate the crosstalk between tumor cells and macrophages and profoundly change the TME. This strategy can be therapeutically utilized in combination with the macrophage therapy approach to induce the immune system to successfully attack the tumor, and should be further explored as a new therapy for the treatment of cancer.